Parabrachial nucleus astrocytes regulate wakefulness and isoflurane anesthesia in mice - Liu, Pei-Chang; Yao, Wei; Chen, Xing-Yu; Su, Wei-Kun; Zheng, Ze-Hong; Yan, Xiong-Bin; Deng, Ya-Ling; Shi, Kai-Ge; Liu, Xin; Gao, Yu-Wei; Lin, Tian-Tian; Zhu, Yun-Xi; et al. (Frontiers in Pharmacology, 2023)
The parabrachial nucleus (PBN) is an important structure regulating the sleep – wake behavior and general anesthesia. Astrocytes in the central nervous system modulate neuronal activity and consequential behavior. However, the role of PBN astrocytes in regulating the sleep-wake behavior and general anesthesia remains unclear. In the present study, combining chemogenetics with electroencephalogram (EEG)/electromyogram (EMG) recording, we showed that the activation of PBN astrocytes increased wakefulness levels hourly for 4 h, while the inhibition of PBN astrocytes decreased total wakefulness levels during the 3 h post-injection period. Chemogenetic activation of PBN astrocytes decreased isoflurane sensitivity and shortened the emergence time from isoflurane-induced general anesthesia. Cortical EEG recordings revealed that PBN astrocyte activation decreased the EEG delta power and burst suppression ratio (BSR) during isoflurane anesthesia.Chemogenetic Inhibition of PBN astrocytes increased the EEG delta power and BSR during isoflurane anesthesia. Taken together, these results indicate that PBN astrocytes are a key neural substrate regulating wakefulness and emergence from isoflurane anesthesia.